Outcome evaluation of the family affairs parenting programme - Siwundla, Lundi (School of Management Studies, 2026)
This study is an outcome evaluation of the Family Affairs programme, a parenting programme offered by Life Choices, a non-profit organisation based in Cape Town, South Africa. Life Choices focuses on parenting skills development through workshops, psychosocial counselling, and job-search counselling services for parents and caregivers. The main aim of the Family Affairs parenting programme is to improve the capacity of parents and caregivers to provide children with competent, quality parenting despite adverse circumstances. Family Affairs offers a four-part multi-component intervention that includes a compulsory one job-search counselling, and establishing or participating in support groups. The evaluation of the outcomes of the Family Affairs parenting programme was aimed at responding to three research questions. The first was whether the programme facilitates parental development, which comprises significant improvements in parents' belief systems, family organisational patterns, communication, and parents' problem-solving skills. The second was whether the programme improves parents' relationships with their children. The third was whether parents' parenting styles improve as a result of participating in the programme. The three constructs of interest in the study were thus parental development, parent–child relationship, and parenting style. A quantitative approach and outcome evaluation design were followed in analysing secondary pre-test–post-test data gathered simultaneously by the Family Affairs programme. For the present study, a total of 306 programme participants in the period 2018 to 2020 were sampled, from which the self-reported data were gathered. Wilcoxon's signed rank test and the Kruskal- Wallis tests were used for the before-and-after comparison and the comparison across cohorts, respectively. A comparison of the scores for self-reported parental self-development, specifically family organisational patterns and problem-solving skills, before and after attending the programme showed significant improvements. There were also self-reported improvements in how parent communicated with their children and their parenting styles. The results of the evaluation show that the Family Affairs programme does produce significantly positive short-term self- perceived improvements in parental self-development, parent–child relationships, and parenting style.